Implementation of E-Government as A Media for Developing Potential Kresnomulyo Village Web Based Mobile - Sofia Ulfa, Lulu (YHMM PUBLISHING, 2023)
This study aims to analyze the impacts of e‑Government implementation in Kresnomulyo Village, Ambarawa District, Pringsewu Regency, and to identify key challenges and sustainability recommendations. Employing a qualitative case study approach, data were collected through in‑depth interviews with village officials, a survey of 75 residents, and a review of digital administrative records. Findings indicate that eGovernment has significantly enhanced public service efficiency-expediting document processing and increasing transparency of financial reporting-while fostering greater citizen participation in village deliberations and raising digital literacy, particularly among younger cohorts. Economically, the village’s digital platform has facilitated product promotion for local SMEs and farmers, contributing to an average income growth of approximately 15% over two years. Despite these benefits, major obstacles persist, including limited internet infrastructure, a digital literacy gap among elderly residents, and insufficient data protection policies. Based on these insights, the study recommends cross‑stakeholder collaboration to strengthen ICT infrastructure, implement ongoing digital skills training, and develop robust information security protocols to ensure that eGovernment in Kresnomulyo Village remains inclusive and sustainable.